Associação entre periodontite e câncer de próstata e níveis de antígeno prostático específico (PSA) - Glayson Pereira Vitor (2024)
Periodontitis has been recognized as a chronic systemic inflammatory stimulus with potential risk for the development or worsening of several systemic health conditions, including prostate diseases. Thus, this study presents two specific research proposals with specific objectives: 1) a case-control study to evaluate the association between periodontitis and prostate cancer (PCA); 2) a systematic review and meta-analysis to evaluate the association between periodontitis and PSA (prostate-specific antigen) levels. The case-control study included 372 individuals, being 152 men with CAP (age 63.02 ± 8.67 years) and 220 controls (age 62.71 ± 8.79 years), selected at the Urology Outpatient Clinic of Hospital Luxemburgo, Belo Horizonte – Minas Gerais. Participants underwent a complete periodontal examination and periodontal status was classified according to the 2018 American Academy of Periodontology and European Federation of Periodontology criteria. CAP staging was performed according to Gleason system scores. The association between CAP and variables of interest was assessed by multivariate logistic regression. Cases had a higher occurrence (p=0.019) and severity (p=0.005) of periodontitis. The occurrence of CAP was associated with educational level <9 years (adjusted OR=1.95), alcohol consumption (adjusted OR=3.46), smoking (adjusted OR=2.53), and periodontitis (adjusted OR=1.76). Regarding CAP severity, Gleason scores 1–2 were associated with periodontitis (adjusted OR=1.90), but Gleason scores 3–5 were not. Furthermore, an increase in PSA levels was observed in the case group with increasing severity of periodontitis (stages). The systematic review was based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines and had the following PECO question: Do men with periodontitis have increased blood levels of PSA? A search was carried out in the PubMed, Embase, Scielo, Web of Sciences, Cochrane Library databases and gray literature until January/2024. Six studies were included, being 4 observational studies and 2 clinical trials. The methodological quality was assessed using the Joana Briggs and ROBINS-I tools and the level of evidence using the GRADE system. Observational studies showed significantly lower PSA levels in individuals without periodontitis (p=0.04). Non-randomized clinical trials did not find changes in PSA levels after non surgical periodontal treatment (p=0.13). In the meta-analysis, individuals with PSA>4.0 ng/ml had more severe periodontitis (OR=1.19 95%CI 0.68–2.09; I2=0%), although not significant. There was a positive correlation between PSA and clinical attachment level (r=0.55 95%CI 0.41–0.66; I2=0.0%). There was no difference in PSA levels before and after periodontal treatment (mean difference -0.18 95%CI -0.94–0.57; I2=0%). Overall, it was concluded that periodontitis was associated with the occurrence of prostate cancer and there was no evidence of a direct association between PSA levels and periodontitis, although observations suggest a possible relationship between the severity of periodontitis, clinical periodontal parameters and PSA.